Plasmids, integrons and the spread of antibiotic resistance - Stokes, Hatch (Henry Stewart Talks, 2008)
A description of the integron/gene cassette system, Integrons in the general environment, Class 1 integron mediated spread of antibiotic resistance genes in pathogens, How class 1 integrons work with plasmids and transposons to spread between cells